Hubungan Asupan Energi dan Protein dengan Kejadian Stunting pada Anak Vegetarian Usia 5-12 Tahun di Komunitas Vegetarian Indonesia: Relationship of Energy and Protein Intake to Stunting Events of Vegetarian Children Aged 5-12 Years Old in Indonesia Vegetarian Community - Fabiola Ainy Ejenia; Waisaktini Margareth Manalu; Ahmad Faridi (UNIVERSITAS NGUDI WALUYO, 2023)
Indonesia is the second highest country in Southeast Asia, Background: Indonesia is the second highest country in Southeast Asia, the prevalence of stunting in toddlers is 31.8% in 2020. The prevalence of stunting in toddlers in DKI Jakarta is 16.8%, and the prevalence of stunting in toddlers aged 0-59 months is 19.7 %. Stunting in toddlers and children (>5-12 years) with a vegetarian diet that occurs is influenced by energy and protein intake. The purpose of this study bas to determinine the relationship between energy and protein intake on the incidence of stunting in vegetarian children aged 5-12 years in the Indonesian Vegetarian Society, Jakarta. This study Led na observasional method with a cross sectional design. Sampling using purposive sampling with a sampel of 43 people. Primary data was obtained using a questionnaire in the form of a gform. Data processing used Chi Square test with 95% confidence level and = 0.05. The results of this study were 93.3% of children who were not stunted and 4.7% of children who were stunted, consumed 86% less energy intake, and 25.6% less protein intake. There was no relationship between energy and protein intake on the incidence of stunting (energy p<1,000 & protein p<1.451). The conclusion of the study is that there is no relationship between energy and protein intake on the incidence of stunting in vegetarian children aged 5-12 years in the Jakarta IVS Community. ABSTRAK Indonesia merupakan negara tertinggi kedua di Asia Tenggara, prevalensi stunting pada balita 31,8% tahun 2020. Prevalensi stunting pada balita di DKI Jakarta sebanyak 16,8%, dan prevalensi stunting pada balita usia 0-59 bulan sebanyak 19,7%. Stunting pada balita dan anak-anak (>5-12 tahun) dengan pola makan vegetarian yang terjadi dipengeruhi oleh asupan energi dan protein. Penelitian ini bertujuan untuk menganalisa hubungan asupan energi dan protein terhadap kejadian stunting anak vegetarian Usia 5-12 Tahun Di Komunitas Indonesia Vegetarian Society Jakarta. Desain Penelitian ini adalah desain Cross Sectional dengan jumlah responden 43 dengan metode Purposive Sampling. Data primer diperoleh menggunakan kusioner dalam bentuk gform. Pengolahan data menggunakan uji Chi Square dengan tingkat kepercayaan 95% dan α = 0.05. Hasil penelitian ini 93.3% anak tidak stunting dan 4.7% anak yang mengalami stunting, konsumsi asupan energi kurang 86%, dan asupan protein kurang 25.6%. Tidak terdapat hubungan antara asupan energi dan protein terhadap kejadian stunting (p<0,05). Kesimpulan pada penelitian adalah tidak ada hubungan antara asupan energi dan protein terhadap kejadian stunting pada anak vegetarian usia 5-12 tahun di Komunitas IVS Jakarta.